Leading with cultural intelligence : the real secret to success - Livermore, David A., 1967- (American Management Association, 2015)
Business today is global - and success requires a new set of skills. Whether you're negotiating with vendors in Asia, exploring potential markets in Africa, or leading a diverse team at home, you don't have to master the nuances of every culture you encounter. This book will show you how to lead effectively in any context. Featuring fresh research, case studies, and statistics on the ROI of improving your cultural intelligence (CQ), this new edition details a powerful, four-step model for becoming more adept at managing across cultures: drive - boost your motivation for and confidence in interacting with other cultures; knowledge - understand the relevance of differences in religion, values, norms, and languages; strategy - plan ahead for unfamiliar cultural settings, but remain flexible if actual experience differs from expectations; and action - successfully adapt your behavior to each situation. - Resumé vydavatel